Twin pregnancy with rupture of cerebral arterio venous malformation with intracranial hemorrhage - S., Bhuvana Preethi; N., Usha Rajesh; Nagarajan, Prasanth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Cerebral AV malformation in pregnancy is a rare condition with a prevalence rate of approximately 0.01-0.5%. It generally presents symptoms at 20-40 years of age most commonly at around 30 years of age. It affects both men and women but more prevalent in women at this age group. We presented a case of primi gravida at 22 weeks of gestation with DCDA type of twin presenting in emergency department with intracranial hemorrhage secondary to rupture of AV malformation.